LEED-NC version 2.2 rating system applications of common structural materials - Maher, J.E.; Kramer, Kimberly Waggle (My University, 2015)
Comprehensive understanding of building materials has been the basis of structural engineering. The rising environmental concern is making sustainability a crucial issue in our society. In creating a sustainable built environment, the architect usually takes the lead role with the mechanical engineer having the key responsibility for energy and water savings. Only recently have structural engineers and civil engineers begun to see the real potential of their contributions. This paper contains information pertaining to the four most common structural materials: reinforced concrete, reinforced masonry, steel, and timber. For each material, the sustainability of the material as defined by the LEED-NC Version 2.2 rating system is discussed. Information is provided on how to attain LEED points for a specific material. Whether the LEED-NC Version 2.2 rating system accurately portrays sustainability of common structural materials or needs further development is discussed in the conclusion. A comparison is provided of the four common structural materials in relation to the rating system.
Maher, J.E., Kramer, K.W.. LEED-NC version 2.2 rating system applications of common structural materials. 2007. Sustainable Construction Materials and Technologies, Taylor and Francis Group.
Keywords: Built environment; Civil engineers; Environmental concerns; Further development; Specific materials; Structural engineer